ANALISIS PENGARUH FINANCIAL TECHNOLOGY, FINANCIAL SELF EFFICACY, SELF CONTROL DAN IMPULSIVE BUYING TERHADAP MANAJEMEN KEUANGAN PRIBADI MAHASISWA - Dwi Selvi Amalia; Anik Yuliati (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: This study aims to analyze the influence of Financial Technology, Financial Self-Efficacy, Self-Control, and Impulsive Buying on students’ personal financial management, with a focus on spending behavior and saving habits. Methods: The sample consisted of 100 university students selected using probability sampling with a simple random sampling approach. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that only Self-Control has a significant effect on personal financial management. In contrast, Financial Technology, Financial Self-Efficacy, and Impulsive Buying did not show a significant influence. Results: These findings highlight that self-control is a key internal factor in shaping prudent financial behavior. The implications emphasize the importance of strengthening psychological aspects, particularly self-control, in financial education and literacy programs for university students. Keywords: Personal Financial Management, Financial Technology, Self-Efficacy, Self-Control, Impulsive Buying, Students